THE VALIDITY OF CHARACTER VALUE SOCIAL SCIENCE LEARNING MEDIAFOR FIFTH-GRADE ELEMENTARY STUDENTS - Yulfia Nora; Jamaris; Sufyarma Marsidin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The implementation of social science learning in elementary schools tends to build cognitive abilities mainly rather than to build the attitude or character of students. In fact, based on the learning material, social science learning has a role in the student’s character building. In addition, the learning media used by teachers tend to be conventional so it is monotonous. The research purpose is to produce and describe social science learning media valued for fifth-grade elementary students. The development method used is Research and Development (R&D). The developmental model used is the ADDIE model developed by Dick and Carry. The research is limited to the developmental stage. The research data collection instrument uses a validity questionnaire sheet. Based on the results of data analysis, it was obtained an average percentage of learning material validity at 97.78%, language validity at 97.78%, and design validity at 93.33% with very valid validity criteria for the three validities. It shows that social science learning media is a feasible character for being one of the social science learning media for fifth-grade elementary students.